Supporting parents in the use of the early start Denver model as an intervention program for their young children with autism spectrum disorder - Waddington, Hannah (Int J Dev Disabil, 2019)
Parents are the logical intervention agents for young children with autism spectrum disorder (ASD). The early start Denver model (ESDM) is a promising early intervention approach for children with ASD that can be implemented by parents. This study evaluated the effects of training parents in the use of the ESDM. We used a non-concurrent multiple probe across participants design to evaluate the effects of providing five mothers of young children with ASD with one hour per week of training for 12 weeks. Outcome measures included mothers use of the ESDM techniques and measures of the children’s levels of engagement and imitation, and expressive language skills. Maintenance of outcomes after one month was also assessed. Results showed four of the five mothers increased the percentage of ESDM techniques that they were using usually or consistently. Four of the five children showed some improvement on at least one of the child outcome measures. This suggests mixed results for supporting parents in the use of the ESDM. Implications and future research directions are discussed.